Selenium deficiency sensitizes the skin for UVB-induced oxidative damage and inflammation which involved the activation of p38 MAPK signaling. (January 2015) - Zhu, Xiaokang; Jiang, Mingdong; Song, Erqun; Jiang, Xiaoji; Song, Yang
Highlights: Selenium deficiency sensitizes UVB-induced oxidative damage. Selenium deficiency sensitizes UVB-induced loss of antioxidant enzyme activities. Selenium deficiency sensitizes UVB-induced H2AX phosphorylation. Selenium deficiency sensitizes UVB-induced proinflammatory cytokine levels. Selenium deficiency sensitizes UVB-induced p38 MAPK signaling. Abstract: Ultraviolet B (UVB) radiation causes oxidative damage and inflammation, and ultimately increases the risk of skin carcinogenesis. Selenium is an essential trace element, previous studies indicated selenium deficiency impairs tissue antioxidant capacity in different experimental models. However, the synergistic effect of selenium deficiency and UVB radiation on skin damage is not clear. In the current study, our data revealed selenium deficiency resulted in further increases of reactive oxygen species (ROS), thiobarbituric acid reactive substances (TBARS) and phosphorylated H2AX levels, decreases of GSH level and antioxidant enzyme activities in UVB-irradiated mice. Selenium deficiency also exacerbated UVB-induced cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), tumor necrosis factor-alpha (TNF-α), interleukin-1beta (IL-1β) and IL-6 mRNA expressions. Mechanism studies indicated that UVB-induced p38 signaling was further elevated in the skin of mice maintained with selenium deficiency diet, compared with those maintained with selenium adequate diet. Our investigation suggested that selenium deficiency diet weakens the antioxidant capacity of UVB-irradiated mice skin, which sensitizes to UV radiation-induced oxidative damage and inflammation.